Building Students' Sewing Equipment Competency In Technology Lessons - Kuliyeva Shahnoza Halimovna; Ne'matova Maksad Amrulloyevna (Zien Journals, 2024)
The article describes the issues of formation of students' technological competences in technology lessons, problems, development of competence formation methodology, factors that serve as a basis for determining the levels of formation of students' technological competences.
Keywords: technology lessons; technological competencies; transformative activity; modernization